Upaya Meningkatkan Hasil Belajar Peserta Didik pada Mata Pelajaran Akidah Akhlak Melalui Metode Lectures Vary - Fatimatuzahroh, Fitri; Nurteti, Lilis; Koswara, S. (Graduate Program, Universitas Islam Darussalam (UID) | Islamic University of Darussalam, 2019)
This study aims to discuss learning planning, learning implementation, and student learning outcomes of Akidah Akhlak subject, specifically material about